The role of insulin resistance in nonalcoholic steatohepatitis and liver disease development – a potential therapeutic target?. (1st February 2016) - Dongiovanni, Paola; Rametta, Raffaela; Meroni, Marica; Valenti, Luca
ABSTRACT: Insulin resistance (IR) is defined by the inability of insulin to exert its metabolic actions, due to impaired activation of intracellular insulin signaling. This condition is caused by genetic defects or by environmental conditions, among which the most common is obesity. Systemic IR determines the development of hepatic fat accumulation, which can progress to nonalcoholic steatohepatitis, cirrhosis and hepatocellular carcinoma, and is a major determinant of liver disease independently of coexisting factors. Therefore, insulin-sensitizing drugs are currently under evaluation to improve steatohepatitis. Indeed, manipulation of nuclear hormone receptors is already under scrutiny for liver disease prevention by amelioration of IR, whereas NOTCH signaling inhibition represents a novel approach. Nevertheless, further research is warranted to better understand the mechanism linking IR to progressive fibrogenesis in the absence of inflammation and to identify novel drug targets.